PENGARUH MEKANISME OWNERSHIP STRUCTURE, FREE CASH FLOW, DAN CORPORATE GOVERNANCE TERHADAP BIAYA KEAGENAN DI SEKTOR CONSUMER GOODS PERIODE 2009-2014. - Ezra Shael (CALYPTRA, 2017)
ABSTRACT- This study aims to determine the mechanisms anything that can reduce or increase agency costs within the company . The sample used in the study is sector firms Consumer goods listed in the Indonesia Stock Exchange during the period 2009-2014. The mechanisms used in this study is Ownership structure , Free cash flow , and Corporate governance that have an influence on the magnitude of agency costs in the company . This study uses Asset utilization ratio as a measure of agency costs . The data are used as research material was analyzed using panel data regression in Eviews 8. Based on the results of the companies in the consumer goods sector during the period 2009-2014 , Board size can reduce agency costs while the Bank 's Board independence and incentives can increase agency costs . Keywords: Agency cost, Ownership structure, Free cash flow, Corporate governance.